DO CEO CHARACTERISTICS REALLY MATTER FOR FIRM PERFORMANCE? EVIDENCE FROM INDONESIA - Made Aditya Budastra; Ishiaka Adamu; Fajar Karunia Putra; I Ketut Budastra (Jurnal Bisnis Terapan, 2023)
The Upper Echelon Theory explains that CEOs with certain characteristics are believed to influence firm results because the CEO plays an important role in the firm as the final decision maker. Thus, this raises the question of how important CEO characteristics are in explaining firm performance, or specifically does it matter or not. Addressing these gaps, this study aims to empirically prove the effect of CEO characteristics on firm performance. CEO characteristics in this study are proxied by tenure and gender. The data analysis technique used is Multiple Linear Regression. Based on an analysis of 102 samples of property and real estate sector companies from 2017-2019 on the IDX, we find that CEO tenure positively affects firm performance, and CEO Gender negatively affects firm performance. These results suggest that the Upper Echelon Theory is still a relevant theory for explaining the importance of top management characteristics in understanding organizational outcomes. Furthermore, companies should consider the characteristics of their CEO because it reflects the organizational outcomes.